Morphological Behavior of Green Onion (Allium fistulosum L.) Irrigated with Saline Water in a Protected Environment - Costa, Julio César Calixto; Melo, Raví Emanoel de; Santos, Cícero Gomes dos; Santos, Luana Kamila dos; Lima, Luiz Eduardo de Melo; Santos, Márcio Aurélio Lins dos (Revista Ambientale, 2024)
To elucidate the tolerance of green onion to high salinity, this study aimed to evaluate the effect of the application of saline water on the irrigation of green onion grown in a protected environment in the Agreste de Alagoas region. The experiment was developed in a protected environment at the Federal University of Alagoas - Arapiraca Campus. The experimental design was entirely randomized, and the treatments were composed of five irrigation blades: one level of salinity and four repetitions. Irrigation occurred daily via drainage lysimeters. Two cultivation cycles of 30 days each were carried out. At the end of each cycle, the following parameters were analyzed: plant height (PH), number of tillers (NT), root length (RT), fresh mass of the aerial part (FMAP), dry mass of the aerial part (DMAP), fresh mass of the root (FMR) and dry mass of the root (DMR). The data were subjected to analysis of variance (ANOVA) via SISVAR 5.6. A statistically significant difference was found, and the Tukey test was applied (p < 0.05). In the first cycle, the variables PH, FMAP and DMR had significant effects on the number of irrigation slides. In the second cycle, only the PH was significant, highlighting the influence of saline irrigation on the increase in this variable. Thus, in both cycles, the PH was the only variable with a significant effect on the number of saline irrigation blades. FMAP and DMR were influenced by the saline water used. Saline irrigation is an alternative for the management of green onion in a protected environment under the conditions of Agreste in the state of Alagoas.